Evaluating and assessing tools in the digital swamp - Fullan, Michael; Donnelly, Katelyn (Solutions for digital learner-centered classrooms., 2015)
This book explores the Digital Swamp Index, helping educators wade through digital innovations in order to uncover tools that truly accelerate student achievement. It can be used to effectively implement technology and address the revolution occurring in education, which is generating a new nature of learning.